Clinical and CBCT assessment of role of bisphosphonate on osteotomy site and implant surface - Amit Singh; A Muthukumarswamy; George Attokaran; Mirna Garhnayak; Lokanath Garhnayak; Lipika Gopal; Naveen Reddy (Wolters Kluwer Medknow Publications, 2024)
Objectives: To assess the role of bisphosphonate on osteotomy site and implant surface. Materials and Methods: Twenty patients with adequate width and height of edentulous space and a single missing posterior tooth between the ages of 25 and 55 were incorporated in this research. Ten participants received implant therapy alone; the other ten patients received implant therapy and bisphosphonate application to osteotomy site and the implant surface. Result: Changes in the crestal bone level were seen in both the study and control groups. At 1 year, crestal bone loss was less in the bisphosphonate-treated group than in the control group. Conclusion: The quantity of crestal bone loss was reduced when bisphosphonate (sodium alendronate) was applied locally near the implant and osteotomy site.